2009
DOI: 10.1093/bja/aep044
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of sufentanil in children for intubation after sevoflurane induction without neuromuscular block

Abstract: Excellent intubation conditions could be obtained in children after inhalation induction with low sevoflurane concentrations and adjuvant sufentanil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Min et al [2] reported that the bolus dose of remifentanil required for successful tracheal intubation was 0.56 ± 0.15 lg/kg in 50% of children during inhalation induction using 5% sevoflurane in the absence of neuromuscular blocking drugs. In addition, the effective dose of sufentanil required for excellent intubation conditions was 0.11 ± 0.07 lg/kg at end-tidal sevoflurane of 3.5% for 50% of children [4]. Considering the equipotent dose of each opioid agent, their results were consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Min et al [2] reported that the bolus dose of remifentanil required for successful tracheal intubation was 0.56 ± 0.15 lg/kg in 50% of children during inhalation induction using 5% sevoflurane in the absence of neuromuscular blocking drugs. In addition, the effective dose of sufentanil required for excellent intubation conditions was 0.11 ± 0.07 lg/kg at end-tidal sevoflurane of 3.5% for 50% of children [4]. Considering the equipotent dose of each opioid agent, their results were consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 87%
“…When difficult intubation is anticipated or airway obstruction occurs, this technique is favored over intravenous induction. Several studies have reported on tracheal intubation conditions during induction of sevoflurane inhalation with variable opioid agents without neuromuscular blockade in children [2,4]. Min et al [2] reported that the bolus dose of remifentanil required for successful tracheal intubation was 0.56 ± 0.15 lg/kg in 50% of children during inhalation induction using 5% sevoflurane in the absence of neuromuscular blocking drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed on a neonatal population are lacking, but some data on children 2-9 years of age, 0.3 μg/kg sufentanil combined with 2.5 mg/ kg of propofol, and vecuronium, effectively blunted the cardiovascular responses to tracheal intubation [ 190 ]. The ED 50 for sufentanil for excellent intubating conditions decreased as the expired fraction of sevofl urane increased in children [ 191 ]. For example, at 3 % of sevofl urane, the ED 50 was 0.32 μg/kg sufentanil.…”
Section: Inhalational Inductionmentioning
confidence: 96%
“…Several strategies have been developed to speed the induction time and improve the quality of tracheal intubation during sevoflurane induction in children, such as extended exposure to sevoflurane,[4] high inspired fraction of sevoflurane,[5] clonidine premedication,[12] and addition of nitrous oxide,[13] opioids,[14151617] or propofol. [18]…”
Section: Introductionmentioning
confidence: 99%